2022
DOI: 10.3390/ijms23179803
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Molecules on Signaling Pathways in Autism Spectrum Disorder

Abstract: The signaling pathways associated with lipid metabolism contribute to the pathophysiology of autism spectrum disorder (ASD) and provide insights for devising new therapeutic strategies. Prostaglandin E2 is a membrane-derived lipid molecule that contributes to developing ASD associated with canonical Wnt signaling. Cyclooxygenase-2 plays a key role in neuroinflammation and is implicated in the pathogenesis of neurodevelopmental diseases, such as ASD. The endocannabinoid system maintains a balance between inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 97 publications
(197 reference statements)
2
11
0
Order By: Relevance
“…As depicted in the COX‐2KO mouse model (Bosetti et al, 2004; Clemente et al, 2020; Li et al, 2010), many developing genes have differential expression due to the reduced PGE 2 levels. This disrupts synaptic transmission pathways, long‐term nerve potentiation, navigating the neurites, and developing the dendritic spine (Rai‐Bhogal et al, 2018; Yui et al, 2022), consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…As depicted in the COX‐2KO mouse model (Bosetti et al, 2004; Clemente et al, 2020; Li et al, 2010), many developing genes have differential expression due to the reduced PGE 2 levels. This disrupts synaptic transmission pathways, long‐term nerve potentiation, navigating the neurites, and developing the dendritic spine (Rai‐Bhogal et al, 2018; Yui et al, 2022), consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, inhibiting PGE 2 production via local injection of COX-2 inhibitors can decrease dendritic tree arborization and excitatory synaptic density (Dean et al , 2012a). The reduced PGE 2 levels, as seen in COX-2KO mouse model (Bosettiet al , 2004;Li et al , 2010;Clemente et al , 2020), lead to differential expression of many developmental genes, disrupting pathways important for synaptic transmission, long-term potentiation, neurite navigation, and formation of dendritic spines (Rai-Bhogal et al , 2018;Yui et al , 2022) , which is consistence with our results.…”
Section: Discussionsupporting
confidence: 89%
“…In ASD pathogenesis, lipid metabolism may play an important role [ 66 ], but the molecular mechanisms are poorly defined. Our findings first revealed that ApoA-I is a hub protein with regard to the lipid metabolism in ASD, where aberrantly upregulated ApoA-I has a negative impact on the core phenotypes of ASD.…”
Section: Discussionmentioning
confidence: 99%